2020
DOI: 10.1212/wnl.0000000000009855
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in patients with psychogenic nonepileptic seizures

Abstract: ObjectiveTo investigate the hypothesis that patients diagnosed with psychogenic nonepileptic seizures (PNES) on video-EEG monitoring (VEM) have increased mortality by comparison to the general population.MethodsThis retrospective cohort study included patients evaluated in VEM units of 3 tertiary hospitals in Melbourne, Australia, between January 1, 1995, and December 31, 2015. Diagnosis was based on consensus opinion of experienced epileptologists and neuropsychiatrists at each hospital. Mortality was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 26 publications
5
81
1
2
Order By: Relevance
“…Further research is warranted in this area, particularly as depression is a driving force for a higher mortality rate among pwPNES. [3][4][5] When the NDDI-E was developed and validated, subjects had to have a 4th grade reading level to minimize errors in the interpretation of the six items. 8 Although intelligence quotient testing was not one of the eight psychometric instruments administered to all patients, we did exclude any patients with a known intellectual disability or reading impairment.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is warranted in this area, particularly as depression is a driving force for a higher mortality rate among pwPNES. [3][4][5] When the NDDI-E was developed and validated, subjects had to have a 4th grade reading level to minimize errors in the interpretation of the six items. 8 Although intelligence quotient testing was not one of the eight psychometric instruments administered to all patients, we did exclude any patients with a known intellectual disability or reading impairment.…”
Section: Limitationsmentioning
confidence: 99%
“…3,4 Similarly, a large cohort study found that 20% of deaths in pwPNES younger than 50 years were attributable to suicide and pwPNES younger than 30 years had an eightfold increase in their standardized mortality rate. 5 Given the significant deleterious impact of depression and anxiety on the well-being of PWE, prompt diagnosis of these comorbidities is crucial and may be facilitated through validated screening instruments. 6,7 Brief screening instruments, such as the Neurological Disorders Depression Inventory for Epilepsy (NDDI-E) and Generalized Anxiety Disorder scale (GAD-7), have been validated for use in PWE and are widely used to screen for depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…For example, two separate studies found patients with functional movement disorders to have similar or greater reductions in quality of life to patients with “organic” movement disorders 17,18 . A recent study also found that patients with PNES have a standardized mortality ratio that is 2.5 times higher than the general population, similar to that of patients with medically refractory epilepsy 19 …”
Section: Overview Of Functional Neurological Disordersmentioning
confidence: 98%
“…17,18 A recent study also found that patients with PNES have a standardized mortality ratio that is 2.5 times higher than the general population, similar to that of patients with medically refractory epilepsy. 19 Recent research into effective treatment practices may help reshape the prognosis of functional disorders. In the case of functional movement disorders, there is increasing evidence to support modified intensive physical rehabilitation programs.…”
Section: Overvie W Of Fun C Tional Neurolog Ic Al Disorder Smentioning
confidence: 99%
“…22 Furthermore, some patients have seizures due to psychiatric disordersparoxysmal nonepileptic seizures-a group that also has a 2.5-fold elevated mortality rate. 23 2.1.2 | Bias toward attributing COD to a…”
Section: General Pathology Findingsmentioning
confidence: 99%